Modelling Moisture Sorption Isotherms of Superabsorbent Polymer Fabric for Desiccant Drying of Crops - Peter Kang’ethe Kimani; Ayub Njoroge Gitau; Duncan Onyango Mbuge; Januarius Ondiek Agullo (Adsorption Science & Technology)
Desiccants are important in the drying of temperature-sensitive grains such as seeds for planting. Superabsorbent polymers (SAPs) have previously been identified for possible application in the drying of crops. Applying the gravimetric technique to measure the sorption isotherms and the effectiveness of the desiccant in crop drying was determined at temperatures 20, 25, 30, 35, 40, 45, 50, and 55°C. Using R statistical software, eleven sorption isotherm models were fitted to the experimental data using the nonlinear regression functions. The coefficients of each model were obtained. The modified Freundlich, modified Henderson, and modified Oswin models best predicted the experimental data for the study temperature range. Using symbolic regression and nonlinear regression in R software, four mathematical models were obtained. R software codes were assembled for the analysis of sorption isotherm models. Compared to the existing models, the developed models were found to give a more statistically accurate association between the temperature, moisture content of SAP fabric, and relative humidity.